Impact of optimal anti-proteinuric therapy on the prevention of diabetic kidney disease progression - Saed Ahmed Ismail; Molla Asnake Kebede; Getachew Wondafrash; Rediet Ambachew; Rukia Abukar Abdi; Elias Tabit Ahmed; Missgana Worku Belete; Misikr Alemu Eshetu; Subah Abderehim Yesuf (Scientific Reports)
Abstract Diabetic kidney disease (DKD) is the leading global cause of end-stage renal disease (ESRD), with its prevalence rising, particularly in resource-limited settings. Antiproteinuric medications are central to DKD management, but their optimal utilization is expected to be low in such settings and remains underexplored in Ethiopia. This study aimed to assess the optimization of antiproteinuric therapy in DKD and its association with proteinuria and estimated glomerular filtration rate (eGFR). A facility-based cross-sectional study was conducted using simple random sampling. Data were entered, coded, and cleaned using Microsoft Excel 2016 and analyzed with SPSS version 26. Descriptive statistics were used to summarize the data, and multiple logistic regression was performed to identify associations between dependent and independent variables. Odds ratios were computed, and a p-value < 0.05 was considered statistically significant. A total of 402 patients participated in the study, yielding a response rate of 95.3%. The majority were male (239; 59.5%), with a median age of 58 years (IQR: 47–65). Among the participants, 307 (76.4%) were receiving ACEIs/ARBs and/or SGLT2 inhibitors, with ACEIs, ARBs, and SGLT2 inhibitors used by 246 (61.2%), 45 (11.2%), and 124 (30.8%) patients, respectively. However, only 163 (40.5%) were taking optimal doses of antiproteinuric agents. Multiple logistic regression revealed that sub optimal utilization of antiproteinuric therapy was significantly associated with increased albuminuria [AOR (95% CI) 1.93 (1.08–3.45)] and eGFR < 15 mL/min [AOR (95% CI) 15.01 (1.72–131.05)]. Suboptimal utilization of anti-proteinuric therapy was a significant factor in increased albuminuria and severely reduced eGFR, both key indicators of worsening of diabetic kidney disease (DKD) progression. Despite this, a large proportion of DKD patients received suboptimal doses.